KAJIAN STRATEGI PERENCANAAN PEMBANGUNAN DAERAH BERBASIS SOSIAL BUDAYA DI KOTA KENDARI - Syahrun Syahrun; Wa Ode Sitti Hafsah; Abdul Alim (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
Unavoidable globalization should be anticipated by implementing the social-cultural based local government development to strengthen self identity and local wisdom as a guide to arrange the strategies of government development. Local government development planning strategy based on social culture in Kendari City is one of appropriate and suitable programs. This paper aims to investigate and to describe local government development planning strategy based on social culture as one of efforts to improve the society’s prosperity. This research employed qualitative approach. The data was obtained from several informants selected purposively. Therefore, the data was analyzed qualitatively, using three simultaneous steps: data reduction, data presentation, and conclusion, with local development planning and culture innovation potency theories. The local government development planning strategy based on social culture in Kendari city shows the existence of interaction between global and local culture and economy. Social culture aspect is believed to support the implementation and development of global network, with good quality and capability. Cultural tradition is very important because it can unify different cultural backgrounds, particularly heterogeneous condition in Kendari; in which each ethnic brings unique and different tradition or culture like Muna, Tolaki, Bugus, Buton, and others. The development strategies implementable are involving custom figure and society’s participation, improving social cultural development, and utilizing local wisdom cultural value in development, and culture-based education.